2020
DOI: 10.1177/1178633720962935
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Early COVID-19 Research: The Top 50 Cited Papers

Abstract: Introduction: The COVID-19 pandemic is rapidly evolving with the number of cases exponentially rising. The research scientific community has reacted promptly as evidenced by an outstanding number of COVID-19 related publications. As the number of scientific publications rapidly rises, there is a need to dissect the factors that lead to highly impactful publications. To that end, the present paper summarizes the characteristics of the top 50 cited COVID-19-related publications that emerged early during the pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 65 publications
2
38
1
5
Order By: Relevance
“…These papers were cited 63 849 times until May 29, 2020. Type of study, journal, number of citations, number of authors, country of publication, and study content were other characteristics studied ( 26 ). Another paper analyzing COVID-19 research activity concluded that due to the pandemic and the high rate of infectivity, there is a global need for more relevant research that can help to be more informed about the clinical and pathogenic characteristics of this disease ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…These papers were cited 63 849 times until May 29, 2020. Type of study, journal, number of citations, number of authors, country of publication, and study content were other characteristics studied ( 26 ). Another paper analyzing COVID-19 research activity concluded that due to the pandemic and the high rate of infectivity, there is a global need for more relevant research that can help to be more informed about the clinical and pathogenic characteristics of this disease ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…The average citation per journal was 28.53; it was above the number of 23.4 citations per article, reported by a study of 2530 publications about scientific impact in the first months of COVID-19 [ 67 ]. These numbers are pretty below a previous report of the top-50 cited COVID-19 related articles in which 18% of articles received more than 2000 citations; also, the general topic of COVID-19 concentrated half of the top-50 cited publications in only three journals (The Lancet, NEJM, and JAMA) [ 68 ]. The most cited journal in our study (Int J Infect Dis) received 674 citations; this number is below the 1192 cites received by the Am J Emergency Medicine in a study that reported top emergency medicine journals in terms of COVID-19 publications in 2020 [ 69 ].…”
Section: Discussionmentioning
confidence: 69%
“…This trend has also evolved to assess the impact of specific medical topics like achalasia [ 1 ], diverse techniques like robotic surgery [ 78 ], and of course, the early impact of COVID-19 [ 64 , 68 ]. However, to the best of our knowledge, there was no previous publication of MRI and PET/CT research trends in COVID patients.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from taking a social perspective, we also touch upon limitations, as well as aspects of bibliometry that are generally not explored in typical studies in this area. For example, several previous works on bibliometric investigations into the pandemic have explored papers originating from specific countries or languages [ 24 , 25 ], or the pandemic from a subject specific perspective [ 26 ], or the exploration of the top N papers [ 27 ]. More general pandemic-related investigations have highlighted aspects such as the most productive authors, the most cited papers, the value of pre-prints, etc.…”
Section: Discussionmentioning
confidence: 99%